German women's writing in the twenty-first century - Baer, Hester; Hill, Alexandra Merley (Studies in German literature, linguistics, and culture., 2015)
"What is the status of women's writing in German today, in an era when feminism has thoroughly problematized binary conceptions of sex and gender? Drawing on gender and queer theory, including the work of Lauren Berlant, Judith Butler, and Michel Foucault, the essays in this volume rethink conventional ways of conceptualizing female authorship and re-examine the formal, aesthetic, and thematic terms in which "women's literature" has been conceived. With an eye to the literary and feminist legacy of authors such as Christa Wolf and Ingeborg Bachmann, contributors treat the works of many of contemporary Germany's most significant literary voices, including Hatice Akyün, Sibylle Berg, Thea Dorn, Tanja Dückers, Karen Duve, Jenny Erpenbeck, Julia Franck, Katharina Hacker, Charlotte Roche, Julia Schoch, and Antje Rávic Strubel -- authors who, through their writing or their role in the media, engage with questions of what it means to be a woman writer in twenty-first-century Germany."--